Retraction Note: Successful clavicle fracture surgery performed under selective supraclavicular nerve block using the new subclavian approach - Hironobu Ueshima; Hiroshi Otake (JA Clinical Reports, 2020)
An amendment to this paper has been published and can be accessed via the original article.